The Winter of Russia's Discontent Russia's Futures from Within and Without. The Conference on Russia Papers 2023 - Šrāders, Sandis; Terry, George Spencer (University of Tartu Press, 2023)
This book aims to trace the different directions that Russia has taken after initiating its full-scale invasion of Ukraine on 24 February 2022. The authors, coming from positions of policy, academia, and practice, employ a transdisciplinary approach to critically engage the question of how Russia as an actor will develop in such an altered paradigm through three lines of argumentation. The first of these themes is centred on Russia's relations with other major powers and how these ligatures might condition future developments in a global perspective. The second topic relates the effect of the 'Russian idea' on domestic dynamics within Russia, as well as with how it has coloured understandings of Russia in the West. Finally, the authors discuss possible future weaknesses for Russia and question whether they will actually be as serious as previously thought. While no singular to the guiding answer can be posited, these dialogues nonetheless contribute to building a solid foundation for discussions within and between transatlantic capitals as well as globally.